Improving the vocational status of patients with long-term mental illness: a randomised controlled trial of staff training. - O'Brien, A; Price, C; Burns, T; Perkins, R (2003)
OBJECTIVE: To investigate the impact of training CMHT members in the practice of Individual Placement and Support on the vocational status of long-term patients. METHOD: Six CMHTs received vocational training by a work co-ordinator; four continued with standard care. The best vocational status of the 1037 subjects was ascertained after one year. Factors associated with improvement in vocational status were identified. RESULTS: There was no difference in change of vocational status. Age, previous employment and diagnosis influenced outcome. CONCLUSION: Training in IPS at team level did not improve employment status. A dedicated, vocational worker appears to be essential for successful IPS.